School Co-Curricular Management System - Muhammad Fyruz Ismat, Azmi (2022)
The School Co-Curricular Management System is a cutting-edge solution designed to automate tracking student attendance in co-curricular activities. The traditional manual methods of record keeping and reporting often lead to errors and inaccuracies, making it difficult for schools to assess student participation in these activities. This system aims to provide a more efficient and accurate solution for managing co-curricular activities. It is developed using web technologies and database management systems, offering a web-based interface for users to access and manage information. The system also utilises a database to store and retrieve all the data records, ensuring the data is secure and easily accessible. The School Co-Curricular Management System has been implemented in Sekolah Kebangsaan Mat Kilau schools and has received positive feedback from teachers and students. The system has significantly reduced the time required to manage co-curricular data and improved the accuracy of co-curricular data records. This solution is user-friendly, secure, and scalable, making it an ideal choice for schools looking to automate the co-curricular process and support student development.